A method for preparing manganese-zinc ferrite material

By combining polythiophene Schiff alkali conductive polymer with lanthanum doped manganese ferrites, a wide-band high-conducting manganese ferrites are solved, and the problem that existing electromagnetic shielding materials cannot meet the invisibility technology requirements is achieved. Broadband absorption and magnetic performance improvements in the frequency band.

CN118824719BActive Publication Date: 2024-12-27NANTONG HUAXING MAGNETIC MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411119185.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-02
Publication Date
2024-12-27
Estimated Expiration
2044-02-02

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of manganese zinc ferrite and discloses a method for preparing a manganese zinc ferrite material. A composite material containing both a "conductive" element and a "magnetic" element is prepared by a physical mixing method. The manganese zinc ferrite has a large resistivity, and electromagnetic waves can easily enter the interior of the material to achieve electromagnetic impedance matching, so that the magnetic loss performance is outstanding; the polythiophene Schiff base conductive polymer can coordinate with metal ions to form a metal complex, thereby increasing the dielectric loss of the composite material and reducing the reflection of electromagnetic waves on the incident interface; the Schiff base structure transfers charges through the conjugation of single and double bonds, and the double bond electron rotation makes it magnetic, and the pinning effect of rare earth lanthanum increases the loss caused by domain wall resonance, thereby effectively improving the magnetic properties and wave absorption performance of the composite material, so that the prepared manganese zinc ferrite material has excellent properties of broadband and high conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application with application number 2024101469871, application date February 2, 2024, and invention name “A broadband and high-conductivity manganese-zinc ferrite material and its preparation method”. Technical Field

[0002] The invention relates to the technical field of manganese-zinc ferrite, in particular to a method for preparing a manganese-zinc ferrite material. Background Art

[0003] With the widespread application of electronic technology, the rapid development and popularization of radio broadcasting, mobile phones, television and microwave technology, electromagnetic radiation has become a new type of pollutant. Electromagnetic waves are extremely harmful to the environment and human body. Therefore, electromagnetic protection has become a hot topic of current research. According to the current development status of absorbing materials, traditional electromagnetic shielding materials mainly achieve the purpose of shielding through the reflection of electromagnetic waves. It is difficult to meet the comprehensive requirements of thinness, width, lightness and strength put forward by the increasingly advanced stealth technology. Therefore, it is necessary to develop a type of protective material with high absorption and low reflection of electromagnetic waves.

[0004] Using absorbing materials in electronic devices can reduce the radiation intensity of electromagnetic waves, thereby reducing electromagnetic pollution and ensuring human health; ferrite as an absorbing material has high magnetic permeability, high coercivity, and a small relative dielectric constant, which is conducive to impedance matching, enhancing the transmission and attenuation of electromagnetic waves, and is expected to achieve microwave absorption in the high-frequency band. However, it has high density, low temperature stability, and low dielectric loss, and still has problems such as narrow absorption band and weak absorption intensity. Therefore, a single ferrite absorbing material cannot meet the requirements of strong absorption and wide bandwidth. Therefore, two electromagnetic wave absorbing materials are often compounded to make the new material have advantages. The conductive polymer has a conjugated long-chain structure, good dielectric properties, and a relatively strong dielectric loss capacity, which can make up for the dielectric loss deficiency of ferrite. For example, patent CN102344648B discloses a conductive polymer / magnetic material composite absorbing material, which is composed of a-ferrite, poly (3, 4-dioxyethyl) thiophene and organic binders such as epoxy resin or polyurethane. The reflection loss value is preferably -17dB, and the absorbing performance is improved to a certain extent, but the absorption bandwidth is still narrow, which is not suitable for applications with high requirements for the absorption bandwidth.

[0005] The present invention first synthesizes a polythiophene conductive polymer containing a Schiff base, then prepares a lanthanum-doped manganese zinc ferrite, and combines the two together using a physical mixing method, retaining the characteristic functional groups of the ferrite and the polymer, and having the characteristics of high absorption intensity, wide absorption bandwidth and excellent magnetic properties. Summary of the invention

[0006] The technical problem solved by the present invention is: to provide a broadband high-conductivity manganese-zinc ferrite material and a preparation method thereof, so as to obtain a new type of wave absorbing material with good magnetic properties and wide absorption frequency band.

[0007] The technical solution of the present invention is:

[0008] A method for preparing a broadband high-conductivity manganese zinc ferrite material. The broadband high-conductivity manganese zinc ferrite material comprises the following components in parts by weight: 70-300 parts of a polythiophene Schiff base conductive polymer and 100 parts of lanthanum-doped manganese zinc ferrite.

[0009] The preparation method is carried out according to the following steps: placing a polythiophene Schiff base conductive polymer and lanthanum-doped manganese zinc ferrite in a beaker, adding tetrahydrofuran, ultrasonically treating for 20-40 minutes, then mechanically stirring for 1-2 hours at a speed of 1500-3000 r / min, after mixing evenly, filtering, washing with deionized water, and drying to obtain a broadband high-conductivity manganese zinc ferrite material.

[0010] Preferably, the preparation method of the lanthanum-doped manganese-zinc ferrite is carried out according to the following steps: iron oxide, manganese oxide, zinc oxide, lanthanum oxide and grain boundary strengthener are added to a ball mill for ball milling, then added to a muffle furnace, pre-fired at a temperature of 850-1000°C for 1-4h, cooled to room temperature with the furnace, followed by secondary ball milling, and then the mixed powder is pressed into shape and sintered at a sintering temperature of 1300-1450°C for 3-5h, and naturally cooled to obtain lanthanum-doped manganese-zinc ferrite.

[0011] Preferably, the grain boundary strengthener is any one of CaCO3, SiO2, and Al2O3.

[0012] Preferably, in parts by weight, iron oxide is 55-65 parts, manganese oxide is 20-35 parts, zinc oxide is 5-15 parts, lanthanum oxide is 0.02-0.2 parts, and grain boundary strengthener is 0.1-0.5 parts.

[0013] Preferably, the preparation method of the polythiophene Schiff base conductive polymer is carried out according to the following steps:

[0014] (1) Add 2-imidazolecarboxaldehyde and N,N-dimethylformamide to the reaction flask, stir evenly, add thiophene-3-amine, stir to react, after the reaction is completed, add deionized water, precipitate, filter, recrystallize from methanol, and dry to obtain thiophene Schiff base intermediate. The preparation process is as follows:

[0015]

[0016] (2) Add ferric chloride and chloroform to the reaction flask, stir evenly, add thiophene Schiff base intermediate and thiophene, stir to carry out polymerization reaction, filter after the reaction, wash with deionized water, and dry to obtain polythiophene Schiff base conductive polymer. The preparation process mechanism is as follows:

[0017]

[0018] Preferably, in the step (1), the amount of 2-imidazolecarboxaldehyde is 100 parts and the amount of thiophene-3-amine is 95-110 parts by weight.

[0019] Preferably, in step (1), the reaction temperature is 20-35° C. and the reaction time is 5-12 h.

[0020] Preferably, in the step (2), by weight, ferric chloride is 300-520 parts, thiophene Schiff base intermediate is 20-65 parts, and thiophene is 100 parts.

[0021] Preferably, in step (2), the polymerization reaction temperature is 25-40°C, and the polymerization reaction time is 8-16h. The beneficial technical effects of the present invention are:

[0022] The invention uses 2-imidazole carboxaldehyde and thiophene-3-amine to react to generate a thiophene Schiff base intermediate, and then the thiophene Schiff base intermediate and thiophene undergo a polymerization reaction under the action of ferric chloride to obtain a polythiophene Schiff base conductive polymer, and then controls the doping amount of lanthanum and adds a grain boundary strengthener to synthesize lanthanum-doped manganese zinc ferrite by a solid phase method, and finally adopts a physical mixing method to ultrasonically mix the polythiophene Schiff base conductive polymer and the lanthanum-doped manganese zinc ferrite to obtain a broadband high-conductivity manganese zinc ferrite material.

[0023] The preparation method is physical mixing method, which does not destroy the organizational structure of any component of polythiophene Schiff base conductive polymer and lanthanum-doped manganese zinc ferrite, retains the characteristic functional groups of ferrite and polymer, contains both "magnetic" elements and "conductive" elements, so that the composite material has both conductivity and magnetic properties; manganese zinc ferrite has a large resistivity, and electromagnetic waves can easily enter the interior of the material to achieve electromagnetic impedance matching, which makes its magnetic loss performance outstanding; there is a chemical bonding effect between polythiophene Schiff base conductive polymer and lanthanum-doped manganese zinc ferrite, which reduces the agglomeration of ferrite nanoparticles to a certain extent, and after adding an appropriate amount of rare earth lanthanum element, certain defects will be formed in the ferrite, which is beneficial to increase the specific surface area of ​​the material, thereby enhancing the magnetic permeability and magnetic properties of the material.

[0024] The polythiophene Schiff base conductive polymer containing heteroatoms will produce reflection loss due to polarization and dielectric loss, and can coordinate with metal ions to form metal complexes, which increases the dielectric loss and complex dielectric constant of the composite material, improves the impedance matching of the composite material, and reduces the reflection of electromagnetic waves on the incident interface; the Schiff base structure in the polymer has good conductivity and excellent coordination ability, and can form coordination with lanthanum ions in manganese zinc ferrite. The Schiff base transfers charge through the conjugation of single and double bonds, and the rotation of its double bond electrons makes it magnetic. The conjugated structure cooperates with metal ions to produce additional polarization ability and new electron transfer characteristics. At the same time, the single electron spin in the metal ion can produce a magnetic loss effect; in addition, the pinning effect of rare earth lanthanum affects the motion of the domain wall, which can increase the loss caused by domain wall resonance, thereby effectively improving the microwave absorption capacity of the composite material.

[0025] The broadband high-conductivity manganese zinc ferrite material prepared by the present invention exhibits more excellent comprehensive wave absorbing ability compared with single-component manganese zinc ferrite and polythiophene Schiff base conductive polymer, and by adjusting the addition amount of the composite polythiophene Schiff base conductive polymer, it is possible to effectively control and improve the absorption intensity and the effective absorption bandwidth, thereby achieving the "thin, light, wide and strong" requirements of the new wave absorbing material, further broadening the application scope of the manganese zinc ferrite material. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] 65 parts of iron oxide, 25 parts of manganese oxide, 15 parts of zinc oxide, 0.02 parts of lanthanum oxide and 0.1 parts of grain boundary strengthener SiO2 by weight are added to a ball mill for ball milling, then added to a muffle furnace, pre-fired at 950°C for 3 hours, cooled to room temperature with the furnace, followed by secondary ball milling, and then the mixed powder is pressed into shape and sintered at a sintering temperature of 1350°C for 4 hours, and naturally cooled to obtain lanthanum-doped manganese-zinc ferrite.

[0029] Example 2

[0030] 63 parts of iron oxide, 20 parts of manganese oxide, 10 parts of zinc oxide, 0.11 parts of lanthanum oxide and 0.3 parts of grain boundary strengthener CaCO3 by weight are added to a ball mill for ball milling, then added to a muffle furnace, pre-fired at 1000°C for 1 hour, cooled to room temperature with the furnace, followed by secondary ball milling, and then the mixed powder is pressed into shape and sintered at a sintering temperature of 1450°C for 3 hours, and naturally cooled to obtain lanthanum-doped manganese-zinc ferrite.

[0031] Example 3

[0032] 60 parts of iron oxide, 30 parts of manganese oxide, 15 parts of zinc oxide, 0.2 parts of lanthanum oxide and 0.5 parts of grain boundary strengthener Al2O3 by weight are added to a ball mill for ball milling, then added to a muffle furnace, pre-fired at 900°C for 3 hours, cooled to room temperature with the furnace, followed by secondary ball milling, and then the mixed powder is pressed into shape and sintered at a sintering temperature of 1300°C for 5 hours, and naturally cooled to obtain lanthanum-doped manganese-zinc ferrite.

[0033] Comparative Example 1

[0034] 65 parts of iron oxide, 25 parts of manganese oxide, 15 parts of zinc oxide and 0.1 parts of grain boundary strengthener SiO2 by weight are added to a ball mill for ball milling, then added to a muffle furnace, pre-fired at 950°C for 3 hours, cooled to room temperature with the furnace, followed by secondary ball milling, and then the mixed powder is pressed into shape and sintered at a sintering temperature of 1350°C for 4 hours, and naturally cooled to obtain manganese-zinc ferrite.

[0035] Comparative Example 2

[0036] 65 parts of iron oxide, 25 parts of manganese oxide, 15 parts of zinc oxide and 0.02 parts of lanthanum oxide by weight are added to a ball mill for ball milling, then added to a muffle furnace, pre-fired at 950°C for 3 hours, cooled to room temperature with the furnace, followed by secondary ball milling, and then the mixed powder is pressed into shape and sintered at a sintering temperature of 1350°C for 4 hours, and naturally cooled to obtain lanthanum-doped manganese-zinc ferrite.

[0037] Saturation magnetic flux density test: Manganese-zinc ferrite is made into a ring with a size of ∅20×15×8mm, and a saturation magnetic flux density test is performed using a BH / μ analyzer at 25°C, 50Hz, and 1200A / m.

[0038] Initial magnetic permeability test: Manganese zinc ferrite was made into a ring with a size of ∅20×15×8mm, wound with 20 turns of wire, and the initial magnetic permeability test was carried out at 25°C, 10mV, and 10kHz using an Agilent 4284A LCR precision tester.

[0039]

[0040] It can be seen from the test data in the above table that with the increase of lanthanum doping amount and grain boundary strengthening agent content of manganese-zinc ferrite, the magnetic permeability and saturation magnetic flux density of manganese-zinc ferrite are greatly improved, and the initial magnetic permeability reaches 15031.4 at the highest. This is because the addition of an appropriate amount of La2O3 can form liquid phase sintering, improve the uniformity of the grain size of the magnet after sintering, promote grain growth, and inhibit the growth of abnormal grains, so that the grain size consistency is good, and its soft magnetic properties are improved to a certain extent, thereby increasing the initial magnetic permeability of the ferrite. Excessive addition of La2O3 will precipitate impurities at the grain boundaries and reduce the magnetic properties of the ferrite. At the same time, the addition of grain boundary strengthening agents CaCO3, SiO2 or Al2O3 mainly exists at the grain boundaries, which can significantly improve the chemical properties of the grain boundaries, prevent grain growth, form a high resistance layer at the grain boundaries, and reduce the relative loss factor.

[0041] As the amount of lanthanum doping increases, the saturation flux density of the ferrite is enhanced. The saturation flux density in Example 2 reaches 550.3 mT, achieving a high saturation flux density of the material while maintaining a high initial magnetic permeability and low power consumption of the material; while in Comparative Example 1, no rare earth lanthanum is doped, and the saturation flux density is only 432.4 mT; in Comparative Example 2, no grain boundary strengthener is added, and the saturation flux density is only 463.1 mT. The low saturation flux density results in poor magnetic properties.

[0042] Example 4

[0043] (1) Add 50 parts by weight of 2-imidazolecarboxaldehyde and N,N-dimethylformamide to a reaction flask, stir evenly, add 50 parts of thiophene-3-amine, react at 25°C for 8 hours, add deionized water, precipitate, filter, recrystallize from methanol, and dry to obtain a thiophene Schiff base intermediate.

[0044] (2) Add 180 parts by weight of ferric chloride and chloroform into a reaction flask, stir evenly, add 20 parts of a thiophene Schiff base intermediate and 40 parts of thiophene, and carry out a polymerization reaction at 35°C. After reacting for 15 hours, filter, wash with deionized water, and dry to obtain a polythiophene Schiff base conductive polymer.

[0045] (3) 70 parts by weight of a polythiophene Schiff base conductive polymer and 100 parts of lanthanum-doped manganese zinc ferrite (prepared in Example 1) were placed in a beaker, tetrahydrofuran was added, and ultrasonic treatment was performed for 25 minutes. Then, mechanical stirring was performed at a speed of 2000 r / min for 1.5 hours. After mixing evenly, the mixture was filtered, washed with deionized water, and dried to obtain a broadband high-conductivity manganese zinc ferrite material.

[0046] Example 5

[0047] (1) Add 100 parts by weight of 2-imidazolecarboxaldehyde and N,N-dimethylformamide to a reaction flask, stir evenly, add 95 parts of thiophene-3-amine, react at 35°C for 5 hours, add deionized water, precipitate, filter, recrystallize from methanol, and dry to obtain a thiophene Schiff base intermediate.

[0048] (2) Add 300 parts by weight of ferric chloride and chloroform into a reaction flask, stir evenly, add 20 parts of a thiophene Schiff base intermediate and 100 parts of thiophene, and carry out a polymerization reaction at 40° C. After reacting for 8 hours, filter, wash with deionized water, and dry to obtain a polythiophene Schiff base conductive polymer.

[0049] (3) 180 parts by weight of a polythiophene Schiff base conductive polymer and 100 parts of lanthanum-doped manganese zinc ferrite (prepared in Example 2) were placed in a beaker, tetrahydrofuran was added, and ultrasonic treatment was performed for 40 minutes. Then, mechanical stirring was performed at a speed of 3000 r / min for 1 hour. After mixing evenly, the mixture was filtered, washed with deionized water, and dried to obtain a broadband high-conductivity manganese zinc ferrite material.

[0050] Example 6

[0051] (1) Add 80 parts by weight of 2-imidazolecarboxaldehyde and N,N-dimethylformamide to a reaction flask, stir evenly, add 88 parts of thiophene-3-amine, react at 20°C for 12 hours, add deionized water, precipitate, filter, recrystallize from methanol, and dry to obtain a thiophene Schiff base intermediate.

[0052] (2) Add 520 parts by weight of ferric chloride and chloroform into a reaction flask, stir evenly, add 65 parts of a thiophene Schiff base intermediate and 100 parts of thiophene, and carry out a polymerization reaction at 25° C. After reacting for 16 hours, filter, wash with deionized water, and dry to obtain a polythiophene Schiff base conductive polymer.

[0053] (3) 300 parts by weight of a polythiophene Schiff base conductive polymer and 100 parts of lanthanum-doped manganese zinc ferrite (prepared in Example 3) were placed in a beaker, tetrahydrofuran was added, and ultrasonic treatment was performed for 40 minutes. Then, mechanical stirring was performed at a speed of 1500 r / min for 2 hours. After mixing evenly, the mixture was filtered, washed with deionized water, and dried to obtain a broadband high-conductivity manganese zinc ferrite material.

[0054] Comparative Example 3

[0055] (3) 70 parts by weight of a polythiophene Schiff base conductive polymer (prepared in Example 4) and 100 parts of manganese zinc ferrite (prepared in Comparative Example 1) were placed in a beaker, tetrahydrofuran was added, and ultrasonic treatment was performed for 25 minutes. Then, mechanical stirring was performed at a speed of 2000 r / min for 1.5 hours. After mixing evenly, the mixture was filtered, washed with deionized water, and dried to obtain a manganese zinc ferrite material.

[0056] Comparative Example 4

[0057] (3) 70 parts by weight of a polythiophene Schiff base conductive polymer (prepared in Example 4) and 100 parts of lanthanum-doped manganese zinc ferrite (prepared in Comparative Example 2) were placed in a beaker, tetrahydrofuran was added, and ultrasonic treatment was performed for 25 minutes. Then, mechanical stirring was performed at a speed of 2000 r / min for 1.5 hours. After mixing evenly, the mixture was filtered, washed with deionized water, and dried to obtain a manganese zinc ferrite material.

[0058] Comparative Example 5 is a polythiophene Schiff base conductive polymer (prepared by Example 4).

[0059] Wave absorbing performance test: The materials to be tested prepared in the embodiments and comparative examples were made into circular samples with an outer diameter of 7 mm, an inner diameter of 3 mm, and a height of 2 mm in a mass ratio of 7:3 with paraffin. The wave absorbing performance of the materials in the frequency range of 2-18 GHz was tested using a network analyzer.

[0060]

[0061] Reflection loss refers to the energy lost when an electromagnetic wave is reflected on the surface of a material. It can be seen from the test data in the above table that in the embodiment, as the content of the polythiophene Schiff base conductive polymer increases, the reflection loss value of the material increases from -28.5dB to -39.5dB, and the maximum bandwidth less than or equal to -10dB reaches 4.8GHz, with high absorption intensity and wide absorption bandwidth. This is because, on the one hand, the polythiophene Schiff base conductive polymer containing heteroatoms has polarization and dielectric loss, which causes reflection loss, and can coordinate with metal ions to form a conjugated polymer metal complex, which increases the dielectric loss and complex dielectric constant of the composite material, improves the impedance matching of the composite material, and reduces the reflection of electromagnetic waves on the incident interface; the conjugated Schiff base structure in the polymer has good conductivity and excellent coordination ability, and can coordinate with the lanthanum ion in the manganese zinc ferrite. The Schiff base can transfer charge by the conjugation of single and double bonds, and the rotation of double bond electrons makes it magnetic. The conjugated structure cooperates with metal ions to produce additional polarization ability and new electron transfer characteristics. At the same time, the single electron spin in the metal ions can produce magnetic loss effect, thereby improving the wave absorption ability; on the other hand, there is a chemical bonding effect between the polythiophene Schiff base conductive polymer and the ferrite, which reduces the agglomeration of ferrite nanoparticles to a certain extent. The composite particles have both conductivity and magnetic properties, and their conductivity increases with the increase of polythiophene content. Electromagnetic waves can be absorbed multiple times by lanthanum-doped manganese zinc ferrite and polythiophene Schiff base conductive polymer, so that the electromagnetic waves incident into the material are absorbed to the maximum extent, preventing the electromagnetic waves from re-entering the space, and improving the wave absorption performance of the composite material.

[0062] Comparative Example 3 is a composite material of manganese zinc ferrite and polythiophene Schiff base conductive polymer without lanthanum, and its reflection loss value is -21.8dB. Comparative Example 4 is a composite material of manganese zinc ferrite and polythiophene Schiff base conductive polymer without grain boundary strengthener, and its reflection loss value is -23.5dB, indicating that the doping of rare earth lanthanum is beneficial to improving the material's absorbing performance. This is because the pinning effect of rare earth lanthanum affects the domain wall movement, which can increase the loss caused by domain wall resonance, thereby effectively improving the microwave absorption capacity of the composite material; Comparative Example 5 is a single-component polythiophene Schiff base conductive polymer, and its reflection loss value is -6.2dB, and its absorbing performance is poor; therefore, in comparison, the composite absorbing performance of polythiophene Schiff base conductive polymer and lanthanum-doped ferrite is more excellent, further improving the effective absorption band and absorption intensity.

[0063] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A method for preparing a manganese-zinc ferrite material, characterized in that: The manganese zinc ferrite material comprises the following components in parts by weight: 70-300 parts of polythiophene Schiff base conductive polymer and 100 parts of lanthanum-doped manganese zinc ferrite; The preparation method is carried out according to the following steps: placing a polythiophene Schiff base conductive polymer and lanthanum-doped manganese zinc ferrite in a beaker, adding tetrahydrofuran, ultrasonically treating for 20-40 minutes, then mechanically stirring for 1-2 hours at a speed of 1500-3000 r / min, after mixing evenly, filtering, washing with deionized water, and drying to obtain a broadband high-conductivity manganese zinc ferrite material; The preparation method of the lanthanum-doped manganese-zinc ferrite is carried out according to the following steps: adding iron oxide, manganese oxide, zinc oxide, lanthanum oxide and a grain boundary strengthener into a ball mill for ball milling, then adding them into a muffle furnace, pre-sintering them at a temperature of 850-1000° C. for 1-4 hours, cooling them to room temperature with the furnace, then performing secondary ball milling, and then pressing the mixed powder into a shape, sintering them at a sintering temperature of 1300-1450° C. for 3-5 hours, and naturally cooling them to obtain lanthanum-doped manganese-zinc ferrite; The preparation method of the polythiophene Schiff base conductive polymer is carried out according to the following steps: (1) Add 2-imidazolecarboxaldehyde and N,N-dimethylformamide to a reaction flask, stir evenly, add thiophene-3-amine, stir to react, after the reaction is completed, add deionized water, precipitate, filter, recrystallize with methanol, and dry to obtain a thiophene Schiff base intermediate; (2) adding ferric chloride and chloroform to a reaction flask, stirring evenly, adding a thiophene Schiff base intermediate and thiophene, stirring to carry out a polymerization reaction, filtering after the reaction is completed, washing with deionized water, and drying to obtain a polythiophene Schiff base conductive polymer; The grain boundary strengthener is any one of CaCO3, SiO2, and Al2O3; In terms of weight, the iron oxide is 55-65 parts, the manganese oxide is 20-35 parts, the zinc oxide is 5-15 parts, the lanthanum oxide is 0.02-0.2 parts, and the grain boundary strengthener is 0.1-0.5 parts.

2. The method for preparing the manganese-zinc ferrite material according to claim 1, characterized in that: In the step (1), the amount of 2-imidazolecarboxaldehyde is 100 parts and the amount of thiophene-3-amine is 95-110 parts by weight.